Comparisons of the physicochemical and functional properties of commercially and traditionally processed sago starch - Mustafa Kamal, M.; Rubiyah, Baini; Shahrol, Mohamaddan; Henry Ragai, A.R.; Soh Fong, L.; Abdul Rahman, N.; Mili, N.; Siti Noor Linda, Taib; Othman, A.K.; Mohammad Omar, Abdullah (EDP Sciences, 2016)
Commercial sago starch was obtained from nearby supermarket while traditional sago starch (lemantak) was obtained from local wet-market. In this study, the physicochemical (moisture content, colour, particle size and microstructure) and functional properties (FT-IR spectrometer) of both types of starch were compared. Traditional sago starch (lemantak) exhibits moisture content two times higher than the commercial sago starch. Providing that commercial sago flour has been bleached in the factory, its LAB value also shows higher value than lemantak. Moreover, the particle size of sago flour is also smaller than lemantak, as the effect of multiple-refining in the factory. Meanwhile, the microstructural analysis shows significant difference that is cluster-form-granule in lemantak and disassociated-form-granule in commercial sago flour, which proof that commercial sago flour has been in an extensive process. Finally, the FT-IR results indicated that both sago flour and lemantak has similar spectrometer patterns but differ in the peak intensities, which also indicates the changes in functional properties of sago flour. Results obtained here show that the modern processing equipment as well as the chemical and drying treatment in factory, had led to the loss in some of the purity and functional characteristic in sago starch